Hip fractures and bone mineral density in the elderly--importance of serum 25-hydroxyvitamin D. - Laufey Steingrimsdottir; Thorhallur I Halldorsson; Kristin Siggeirsdottir; Mary Frances Cotch; Berglind O Einarsdottir; Gudny Eiriksdottir; Sigurdur Sigurdsson; Lenore J Launer; Tamara B Harris; Vilmundur Gudnason; Gunnar Sigurdsson (PLoS ONE)
Background The significance of serum 25-hydroxyvitamin D [25(OH)D] concentrations for hip fracture risk of the elderly is still uncertain. Difficulties reaching both frail and healthy elderly people in randomized controlled trials or large cohort studies may in part explain discordant findings. We determined hazard ratios for hip fractures of elderly men and women related to serum 25(OH)D, including both the frail and the healthy segment of the elderly population. Methods The AGES-Reykjavik Study is a prospective study of 5764 men and women, age 66-96 years, based on a representative sample of the population of Reykjavik, Iceland. Participation was 71.8%. Hazard ratios of incident hip fractures and baseline bone mineral density were determined according to serum concentrations of 25(OH)D at baseline. Results Mean follow-up was 5.4 years. Compared with referent values (50-75 nmol/L), hazard ratios for hip fractures were 2.24 (95% CI 1.63, 3.09) for serum 25(OH)D <30 nmol/L, adjusting for age, sex, body mass index, height, smoking, alcohol intake and season, and 2.08 (95% CI 1.51, 2.87), adjusting additionally for physical activity. No difference in risk was associated with 30-50 nmol/L or ≥75 nmol/L in either model compared with referent. Analyzing the sexes separately, hazard ratios were 2.61 (95% CI 1.47, 4.64) in men and 1.93 (95% CI 1.31, 2.84) in women. Values <30 nmol/L were associated with significantly lower bone mineral density of femoral neck compared with referent, z-scores -0.14 (95% CI -0.27, -0.00) in men and -0.11 (95% CI -0.22, -0.01) in women. Conclusions Our results lend support to the overarching importance of maintaining serum 25(OH)D above 30 nmol/L for bone health of elderly people while potential benefits of having much higher levels could not be detected.